COMMUNITY HABIT IN UTILIZING STEM TEBO RIVER AT TANAH TUMBUH DISTRICT OF BUNGO REGION - PRIMA PUTRI, SILVIA; Drs. Dasrizal, MP, Drs. Dasrizal, MP; Thesiwati, SP., M.Si, Aslan Sari (STKIP PGRI Sumbar, 2014)
ABSTRACT This study aims to determine Community Habits Utilizing Stem Tebo River at Tanah Tumbuh district of Bungo Region.This research is a descriptive correlational. Population in this study were all heads of households or families, live between ± 100 m from Tebo river at Tanah Tumbuh district Bungo Region totaling 2.570 households. Samples taken with a random sampling technique by 5 % so that the sample is 129 households.The results of the study found that : 1 ) There is a correlation between education and habits of the people utilizing Tebo river at Tanah Tumbuh district of Bungo Region because of t > t table ; ( 5,505 > 1,662), the strength of the relationship was ( r = 0,439 ) and a very small contribution (19,3%), (2) There is a correlation between with family members exploit peoples habits at Tebo river at Tanah Tumbuh district of Bungo Region because of t > t table ; (-2,847> -1,662), low relationship strength (r = 0,246) and a very small contribution (6,0%) and (3) There is a correlation between education and number of family members to take advantage of peoples habits Tebo river at Tanah Tumbuh district of Bungo Region because of F > F table ( 20.499 > 2.78), strength of the relationship was (r = 0.497) and a small contribution (24,7 % )